Is There a Doctor on Board? - Volozhanina, MD, Elena (North American Journal of Medicine and Science, 2010)
We were somewhere in the middle of Atlantic Ocean when the captain of the airplane announced: “Is there a doctor on the plane?” I thought to myself: “I don’t like flying, forget doing anything else, there must be at least one more doctor on this plane; I am not the only one … At least, I need a colleague…” I counted to three, got up and went to the stewardess: “I’m a doctor”.